Impact of the duration of normothermic regional perfusion on the results of liver transplant from controlled circulatory death donors: A retrospective, multicentric study. Issue 2 (30th November 2021) - Barbier, Louise; Guillem, Thomas; Savier, Eric; Scatton, Olivier; Dondero, Federica; Si Larbi, Anne‐Gaëlle; Bucur, Petru; Sulpice, Laurent; Robin, Fabien; Goumard, Claire; Muller, Xavier; Venhard, Jean‐Christophe; et al.
Abstract: In France, the program of controlled donation after circulatory death (cDCD) was established with routine use of in situ normothermic regional perfusion (NRP). There is currently no consensus on its optimal duration. The purpose was to assess the impact of NRP duration on liver graft function and biliary outcomes. One‐hundred and fifty‐six liver recipients from NRP‐cDCD donors from six French centers between 2015 and 2019 were included. Primary endpoint was graft function assessed by early allograft dysfunction (EAD, according to Olthoff's criteria) and MEAF (model for early allograft function) score. Overall, three (1.9%) patients had primary non‐function, 30 (19.2%) patients experienced EAD, and MEAF score was 7.3 (±1.7). Mean NRP duration was 179 (±43) min. There was no impact of NRP duration on EAD (170±44 min in patients with EAD vs. 181±42 min in patients without, P  = .286). There was no significant association between NRP duration and MEAF score ( P  = .347). NRP duration did neither impact on overall biliary complications nor on non‐anastomotic biliary strictures (overall rates of 16.7% and 3.9%, respectively). In conclusion, duration of NRP in cDCD donors does not seem to impact liver graft function and biliary outcomes after liver transplantation. A 1 to 4‐h perfusion represents an optimal time window.